Barbados : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that Barbados compares favorably with other Caribbean countries on economic and social indicators. The economy is heavily dependent on tourism and financial services. The population is about 272,000, and per capita income is about USD 15,700. Poverty rates are the lowest in the Caribbean. Structural reforms have advanced in taxation, telecommunications, and the public enterprise sector. Corporate and personal tax rates have been further lowered, in line with the multiyear reduction in these rates initiated in FY2002/03.